Survei Minat Belajar Penjas dan Tingkat Kesegaran Jasmani Siswa Kelas X di SMK Pamor Cikampek Pada Masa Pandemi Covid 19 - Rizki Agus Pramana; Rekha Ratri J; M. Mury Syafei (Peneliti.net, 2021)
This study aims to determine the interest in learning physical education and the level of physical fitness of class X students at SMK Pamor Cikampek during the covid 19 pandemic. The research method used a survey method with questionnaires and physical fitness tests. For interest in physical education, there are categories of